Kajian Beberapa Sifat Kimia Tanah Pada Beberapa Tipe Penggunaan Lahan: Study of Some Soil Chemical Properties in Several Different Land Uses - Margaretta, Debora; Mahbub, Itang Ahmad; Ermadani, Ermadani (Jurnal Silva Tropika, 2026)
ABSTRACT Soil chemical properties have a crucial role in determining soil fertility. Land use is one factor that determines soil chemical properties. The purpose of this study was to examine several soil chemical properties across different land uses. The study was conducted in Muhajirin Village, Jambi Luar Kota District, Muaro Jambi Regency, from March to May 2025. Soil sampling was conducted in oil palm, rubber, and areca nut plantations. The soil type at the study site is classified as an Ultisol with a slope of 3-8%. For each land use, a main plot and subplots were identified for soil sampling. Soil samples were taken at a depth of 0-30 cm using a soil auger. Soil chemical parameters included pH, organic carbon, total nitrogen, available phosphorus, and extra potassium. The results showed that soil pH across the three land use types was relatively similar, while the organic carbon, total nitrogen, and exchangeable potassium content in areca nut plantations was higher than in oil palm and rubber plantations. The soil available phosphorus content in oil palm plantations was higher than in areca nut and rubber plantations. Higher organic C content in the soil also indicates higher total N and exchangeable K content in areca nut plantations, while higher available P content in oil palm plantations is due to the application of phosphate fertilizer. The study aimed to examine the chemical characteristics of the soil under several different land uses.   Keywords: soil chemical properties, different land use   ABSTRAK Sifat kimia tanah memiliki peran penting dalam menentukan kesuburan tanah. Penggunaan lahan merupakan salah satu faktor yang menentukan sifat kimia tanah. Tujuan penelitian ini adalah untuk mengkaji beberapa sifat kimia tanah di berbagai penggunaan lahan. Penelitian ini dilakukan di Desa Muhajirin, Kecamatan Jambi Luar Kota, Kabupaten Muaro Jambi, dari Maret hingga Mei 2025. Pengambilan sampel tanah dilakukan di perkebunan kelapa sawit, karet, dan pinang. Tipe tanah di lokasi penelitian diklasifikasikan sebagai Ultisol dengan kemiringan 3-8%. Untuk setiap penggunaan lahan, petak utama dan sub petak ditentukan untuk pengambilan sampel tanah. Sampel tanah diambil pada kedalaman 0-30 cm menggunakan bor tanah. Parameter kimia tanah meliputi pH, karbon organik, nitrogen total, fosfor tersedia, dan kalium dapat ditukar. Hasil penelitian menunjukkan bahwa pH tanah di ketiga tipe penggunaan lahan relatif sama, sedangkan kandungan karbon organik, nitrogen total, dan kalium yang dapat dipertukarkan di perkebunan pinang lebih tinggi daripada di perkebunan kelapa sawit dan karet. Kandungan fosfor tersedia dalam tanah di perkebunan kelapa sawit lebih tinggi dibandingkan di perkebunan pinang dan karet. Kandungan C organik yang lebih tinggi dalam tanah juga menunjukkan kandungan N total dan K yang dapat dipertukarkan lebih tinggi di perkebunan pinang, sedangkan kandungan P tersedia yang lebih tinggi di perkebunan kelapa sawit disebabkan oleh pemberian pupuk fosfat. Penelitian bertujuan untuk mengkaji karakteristik sifat kimia tanah pada beberapa penggunaan lahan yang berbeda.   Kata kunci: sifat kimia tanah, penggunaan lahan yang berbeda